2023
DOI: 10.3390/medicina59091550
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammatory Cytokines in Rheumatoid Arthritis and Development of Atherosclerosis: A Review

Dražen Bedeković,
Ivica Bošnjak,
Sandra Šarić
et al.

Abstract: Uncontrolled chronic inflammation results in cardiovascular disease and early death. In this review, we studied the impact of rheumatoid arthritis on the cardiovascular system, including the early and accelerated development of atherosclerosis and its clinical manifestations, focusing on the inflammatory mechanisms leading to arterial wall damage, rapid atherosclerotic plaque formation, and thrombosis. Furthermore, the effect of medications used to treat rheumatoid arthritis on the cardiovascular system was st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 150 publications
(373 reference statements)
0
8
0
Order By: Relevance
“…These cytokines not only participate in synovial development but also promote the activation of endothelial cells, leading to dysfunction and accelerating the progression of atherosclerosis through the modulation of inflammatory cascades 33,35 . Moreover, RA chronic inflammation also has procoagulant and prooxidant effects, increasing the expression of tissue factor adhesion molecules, reducing the synthesis of nitric oxide and thrombomodulin, and inducing nicotinamide adenine dinucleotide phosphate oxidase-mediated mechanisms 36,37 . This further leads to endothelial dysfunction and shifts the hemostatic balance of RA toward a prothrombotic state.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines not only participate in synovial development but also promote the activation of endothelial cells, leading to dysfunction and accelerating the progression of atherosclerosis through the modulation of inflammatory cascades 33,35 . Moreover, RA chronic inflammation also has procoagulant and prooxidant effects, increasing the expression of tissue factor adhesion molecules, reducing the synthesis of nitric oxide and thrombomodulin, and inducing nicotinamide adenine dinucleotide phosphate oxidase-mediated mechanisms 36,37 . This further leads to endothelial dysfunction and shifts the hemostatic balance of RA toward a prothrombotic state.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of women with rheumatoid arthritis (RA), an autoimmune inflammatory disease, are also prone to developing cardiovascular disease [70][71][72][73]. Of interest is the fact that ~70% of female RA patients undergo a remission of their disease when pregnant and disease activity is also influenced by the menstrual cycle (reviewed in [74]).…”
Section: Variables and Factors Influencing Post-menopause Diseases An...mentioning
confidence: 99%
“…Studies have shown that TNF-α inhibition significantly improves vascular function in RA patients [ 21 ]. Inflammatory cytokines, immune cells and many others play vital roles in both RA and the development of AS [ 22 , 23 ]. Latest research indicates a positive association between genetic predisposition to RA and high risk of coronary AS.…”
Section: Introductionmentioning
confidence: 99%